Pengaruh Work Life Balance dan Stres Kerja Terhadap Kinerja Karyawan Pada PT Bank Sulselbar Kantor Cabang Majene - Sadir, Sadir; Nadir, Muhammad; Permata, Sri Utami; Fitriani, Nur (Jurnal Manarang Manajemen dan Bisnis, 2022)
The purpose of this study was to determine whether work life balance and work stres partially affect employee performance, whether work life balance and work stres simultaneously affect employee performance. This research was conducted at PT Bank Sulselbar Majene Branch Office. Because every agency in carrying out its activities and to achieve goals is always faced with a problem both coming from within and outside the agency. This study uses a saturated sample where the population is used as a research sample of 36 samples. This research approach uses a quantitative approach with the aim of survey research. In collecting data the researchers used primary data in the form of questionnaire data addressed to employees of PT Bank Sulselbar Majene Branch Office. This study uses multiple linear analysis (Multiple regression analysis). The results show that: 1) There is a significant effect of work life balance partially on employee performance 2) There is a significant effect of partial work stres on employee performance 3) work life balance and work stres simultaneously have a significant effect on employee performance at PT Bank Sulselbar Branch Office Majene